If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-11=8(n-2)+5(1+6n)
We move all terms to the left:
-11-(8(n-2)+5(1+6n))=0
We add all the numbers together, and all the variables
-(8(n-2)+5(6n+1))-11=0
We calculate terms in parentheses: -(8(n-2)+5(6n+1)), so:We get rid of parentheses
8(n-2)+5(6n+1)
We multiply parentheses
8n+30n-16+5
We add all the numbers together, and all the variables
38n-11
Back to the equation:
-(38n-11)
-38n+11-11=0
We add all the numbers together, and all the variables
-38n=0
n=0/-38
n=0
| t²-4t-5=0 | | 2x3=x | | -4d=-6d+2d | | -1/4x=-25 | | -10=8(x+2)-3(x-3) | | 34=19-5x2 | | -9=t | | 252.17=15.1p | | 9(x+4)^2-16=0 | | 0=-2(1+6b)+6(4+2b) | | 5+6f=+5 | | -45=x+19 | | 0.4x=-1.8 | | 3+5x-7x-4=-49 | | 55+4x=75 | | (4x+3)+(2x+9)=18- | | 9(x+4)^2+16=0 | | 8(m-7)-8(m+1)=-64 | | 15x-25=180 | | 4-4(3a+3)=16 | | -9-q=-9-9 | | 4(2m-6)=16 | | -4x-2=-6x+4 | | -4c+20=0 | | n/6-18=2 | | 22+5g=72 | | 5x-2x+8=20 | | 7x+5-3x=3=27 | | -120=6(-3x-2) | | 180=3(-8m-4)0 | | q2-26q=60 | | 6n–3=-87 |